1999
DOI: 10.1152/ajpcell.1999.277.6.c1239
|View full text |Cite
|
Sign up to set email alerts
|

PKC-ε regulates basolateral endocytosis in human T84 intestinal epithelia: role of F-actin and MARCKS

Abstract: Protein kinase C (PKC) and the actin cytoskeleton are critical effectors of membrane trafficking in mammalian cells. In polarized epithelia, the role of these factors in endocytic events at either the apical or basolateral membrane is poorly defined. In the present study, phorbol 12-myristate 13-acetate (PMA) and other activators of PKC selectively enhanced basolateral but not apical fluid-phase endocytosis in human T84 intestinal epithelia. Stimulation of basolateral endocytosis was blocked by the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 45 publications
4
72
1
Order By: Relevance
“…Thus, formation of the PKCε-Lck module is crucial for the cardioprotective effects afforded by both chronic (PKCε transgenesis) and acute (ischemic preconditioning) activation of PKCε. Insofar as ischemic preconditioning represents a highly conserved biological response (having been described in the brain, kidney, gut, skeletal muscle, and liver) (1)(2)(3)9) and is the most powerful cardioprotective intervention identified thus far, the present results have broad implications for our understanding of ischemia/reperfusion injury and protection against tissue injury in general.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Thus, formation of the PKCε-Lck module is crucial for the cardioprotective effects afforded by both chronic (PKCε transgenesis) and acute (ischemic preconditioning) activation of PKCε. Insofar as ischemic preconditioning represents a highly conserved biological response (having been described in the brain, kidney, gut, skeletal muscle, and liver) (1)(2)(3)9) and is the most powerful cardioprotective intervention identified thus far, the present results have broad implications for our understanding of ischemia/reperfusion injury and protection against tissue injury in general.…”
Section: Discussionmentioning
confidence: 72%
“…The role of PKCε as an essential protective kinase against ischemia was first demonstrated in cardiac tissue (4,5,(11)(12)(13). It has subsequently been shown that PKCε not only mediates protective signals in the heart but also functions as a protective kinase against ischemic injury in the gut (9), as an antiapoptotic kinase in the thyroid (6), and as a key molecule to precondition neurological functions in the brain (3,29,30), supporting a ubiquitous role for this enzyme in alleviating the consequences of ischemia. However, the precise molecular mechanisms by which this kinase exerts its salubrious effects remain largely undefined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in several specific examples, MARCKS colocalizes with F-actin, and dissociation from actin is temporally associated with alterations in actin dynamics (22,23), or MARCKS localization is altered after treatment that disrupts actin filaments (18,22). Such data are most readily interpreted as direct effects of MARCKS on actin.…”
mentioning
confidence: 99%